2011
DOI: 10.1002/sim.4337
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of multiple cancer prognosis studies with gene expression measurements

Abstract: Although in cancer research microarray gene profiling studies have been successful in identifying genetic variants predisposing to the development and progression of cancer, the identified markers from analysis of single datasets often suffer low reproducibility. Among multiple possible causes, the most important one is the small sample size hence the lack of power of single studies. Integrative analysis jointly considers multiple heterogeneous studies, has a significantly larger sample size, and can improve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…Under the sparsity condition, many MTL studies have adopted the group Lasso to achieve a common set of features for multiple datasets (Argyriou et al, 2008; Lounici et al, 2009; Liu et al, 2009; Yuan et al, 2012). As the MCP-based group selection outperforms the Lasso-based (Ma et al, 2011), we adopt the group MCP for MTL analysis. The third method for comparison is the composite MCP, which can provide direct insights into the newly developed penalty.…”
Section: Simulation Studymentioning
confidence: 99%
“…Under the sparsity condition, many MTL studies have adopted the group Lasso to achieve a common set of features for multiple datasets (Argyriou et al, 2008; Lounici et al, 2009; Liu et al, 2009; Yuan et al, 2012). As the MCP-based group selection outperforms the Lasso-based (Ma et al, 2011), we adopt the group MCP for MTL analysis. The third method for comparison is the composite MCP, which can provide direct insights into the newly developed penalty.…”
Section: Simulation Studymentioning
confidence: 99%
“…In Huang et al (2012c) and Ma et al (2011a, 2011b), the homogeneity model is adopted to describe the genomic basis of M datasets. We briefly describe this model here for integrity of this article.…”
Section: Integrative Analysis Of Cancer Prognosis Studiesmentioning
confidence: 99%
“…Recent studies have shown that pooling and analyzing multiple studies may effectively increase sample size and improve properties of the identified markers (Guerra and Goldsterin 2009). For example, simulation and data analysis have shown that markers identified in multi-dataset analysis may have more true positives, fewer false positives, and better prediction performance (Ma, Huang and Moran 2009; Ma, Huang and Song 2011a; Ma et al 2011b). Multi-dataset methods include meta-analysis and integrative analysis methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations